2020
DOI: 10.1039/d0cc04279j
|View full text |Cite|
|
Sign up to set email alerts
|

Thermo- and electro-switchable Cs⊂{Fe4–Fe4} cubic cage: spin-transition and electrochromism

Abstract: A mixed valence Cs{Fe4-Fe4} cyanido-cube was synthesized and structurally characterized. The molecule, which is robust in solution, shows a remarkable electronic versatility. Electrochromic properties associated with nine different electronic states...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 17 publications
1
43
0
Order By: Relevance
“…[38, 40,52] Moreover, FeCo distances corresponding to the edges of the cubic units are particularly visible with the intense peak located at 4.95 Å, while those arising from the cube face diagonal observed at around 7 Å, are barely detectable within the two samples. Finally, at higher r, the PDF fades as expected for short-range ordering.…”
Section: Structural Characterizationmentioning
confidence: 99%
“…[38, 40,52] Moreover, FeCo distances corresponding to the edges of the cubic units are particularly visible with the intense peak located at 4.95 Å, while those arising from the cube face diagonal observed at around 7 Å, are barely detectable within the two samples. Finally, at higher r, the PDF fades as expected for short-range ordering.…”
Section: Structural Characterizationmentioning
confidence: 99%
“…33 Later, Glatz decorated a partly reduced cube with the Cs@{Fe II,LS 4 -Fe III,HS 3 Fe II,HS } core, in which the only high-spin Fe(II) center exhibited SCO behaviour. 34 Different from the normally observed charge-transfer induced spin transition (CTIST) in the heterometallic Fe/Co compounds, 35,36 the CT and spin transition (ST) processes may proceed more separately in the Fe-Fe system, whereas more efforts are needed to figure out how it works. [41][42][43]…”
Section: Introductionmentioning
confidence: 96%
“…Recent comprehensive academic studies have shown that some of the excellent tricyanidoferrate(III) anions ([(Tp R )Fe(CN) 3 ] − , Tp R = poly(pyrazol-1-yl)borate) have been used in the construction of SCO materials because their ligand fields and redox potentials can be methodically tuned to a wide range using different substitution groups on the pyrazole ring. 56,57 Based on this type of unit, a series of [(Tp R )Fe(CN) 3 ] − -based complexes have been constructed, such as {Fe III 2 Fe II } trinuclears, 57 {Fe III 2 Fe II 2 } squares, 40,56 {Fe III 4 Fe II 4 } cubic cages, 58,59 and {Fe III 2 Fe II } n one-dimensional (1D) chains. 60,61 Most of the complexes with spin-crossover properties usually change their spin only at the Fe II site.…”
Section: Introductionmentioning
confidence: 99%